Building a Plant DNA Barcode Reference Library for a Diverse Tropical Flora: An Example from Queensland, Australia - Craig M. Costion (Diversity, 2016)
A foundation for a DNA barcode reference library for the tropical plants of Australia is presented here. A total of 1572 DNA barcode sequences are compiled from 848 tropical Queensland species. The dataset represents 35% of the total flora of Queensland’s Wet Tropics Bioregion, 57% of its tree species and 28% of the shrub species. For approximately half of the sampled species, we investigated the occurrence of infraspecific molecular variation in DNA barcode loci rbcLa, matK, and the trnH-psbA intergenic spacer region across previously recognized biogeographic barriers. We found preliminary support for the notion that DNA barcode reference libraries can be used as a tool for inferring biogeographic patterns at regional scales. It is expected that this dataset will find applications in taxonomic, ecological, and applied conservation research.